Analysis of Regional Regulation of Sragen Regency Number 07 of 2015 concerning Protection and Empowerment of Farmers - Rossita Trijaya Novia; Vicki Dwi Purnomo; Edi Prianto; Kelik Endro Suryono; Aida Dewi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The protection and empowerment of farmers aims to realize the sovereignty and independence of farmers in order to increase the level of welfare, quality, and a better life, provide certainty for farming, protect farmers from price fluctuations, high-cost economic practices, and crop failure. Improving the ability and capacity of farmers as well as farmer institutions in carrying out productive, advanced, modern and sustainable farming businesses and developing agricultural financing institutions that serve the interests of farming businesses. In this study the authors analyzed whether the program was running in accordance with Regional Regulation No. 7 of 2015, from an analytical study some of the programs had been running but were not optimal.